The Relationships Between Burnout, Job Satisfaction, and Emotion Regulation Among Foreign Language Teachers: A Meta-Analytic Review - Qikai Wang; Yang Gao; Xiaochen Wang (Acta Psychologica)
This meta-analytic review examines the relationships between foreign language teachers’ burnout and two key factors: (1) job satisfaction and (2) emotion regulation. The analysis incorporates data from 14 studies with 3,812 participants to quantify these relationships and explore potential moderating factors. The results indicate a significant negative correlation between burnout and job satisfaction, as well as a strong negative correlation between burnout and emotion regulation. Moderator analyses reveal that country, educational setting, and education stage significantly influence these relationships. However, continuous moderators such as gender distribution and publication year did not significantly affect the outcomes. These findings underscore the importance of considering contextual factors in addressing burnout among foreign language teachers and suggest targeted interventions to enhance emotion regulation and job satisfaction in this population.